One river, one planning, and one integrated management policy for flood-free - Rahmat Salam; Izzatusolekha; Tria Patrianti; Muhammad Iqbal; Fithria Sari Andalas; Ardan Syukur (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Greater Jakarta, a densely populated metropolitan area, continues to face persistent and complex flooding challenges. Despite flood control efforts in the environmental sector, these initiatives remain fragmented and lack integration. This research aims to integrate river management policies to reduce flood risks in Greater Jakarta, a critical economic region. By developing a cohesive approach, the study seeks to formulate effective mitigation strategies focused on sustainable river management planning, enhanced coordination among stakeholders, and the development of adaptive flood management solutions. The research proposes an innovative model for integrated flood management under the concept of